NILAI-NILAI KEBAJIKAN: KEBAIKAN HATI, LOYALITAS, DAN KESALEHAN DALAM KONTEKS BUDAYA MELAYU - Anatassia, Dede Fitriana; Milla, Mirra Noor; El Hafiz, Subhan (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2015)
Abstract — The belief in good values that live in the community have an influence on the individual’s behavior. Virtue is one of them. Virtues found to have links with the individual’s character and personality. By using the approach of constructive realism indigenous psychology, this study aims to explore the virtues in the context of Melayu culture. Data collection techniques in this study were open ended questions and multiple responses. Data were analyzed with qualitative and quantitative methods using NVivo. It was found that kindness and loyalty are the core virtues that are considered important in everyday life. In the relationship context, the behaviors target of these values is higher in the community than personal. Virtues was found to be differ according to the demands of the situation. These virtues shifted in problem solving situations, where kindness and empathy are expected to appear less than serenity and resourceful. It is clear that the virtues which embraced by the individual does not always manifest if the situation is not supportive for the emergence of these virtues. Abstrak — Kepercayaan pada nilai-nilai kebaikan yang hidup dalam masyarakat memiliki pengaruh pada perilaku individu. Nilai-nilai kebajikan adalah salah satunya. Nilai kebajikan ditemukan memiliki kaitan dengan karakter dan kepribadian seseorang. Dengan menggunakan pendekatan realisme konstruktif indigenous psychology, studi ini bertujuan menggali nilai-nilai kebajikan dalam konteks budaya Melayu. Penelitian ini menggunakan teknik pengumpulan data open ended question dan multi respon. Data dianalisis dengan metode kualitatif dan kuantitatif dengan menggunakan NVivo. Ditemukan bahwa nilai-nilai kebaikan hati dan loyalitas merupakan nilai-nilai utama yang dianggap penting dalam kehidupan sehari-hari. Dalam konteks relasi, target pengamalan perilaku dari nilai-nilai tersebut lebih tinggi pada komunitas dibandingkan personal. Nilai-nilai kebajikan ditemukan berbeda sesuai dengan tuntutan situasi. Nilai-nilai tersebut bergeser dalam situasi penyelesaian masalah, dimana kebaikan hati dan empati lebih sedikit diharapkan muncul dibandingkan ketenangan (serenity) dan kepandaian (resourceful). Hal ini menjelaskan bahwa nilai-nilai yang dianut oleh individu tidak selalu manifes jika situasinya tidak mendukung bagi munculnya nilai tersebut.